Jesse Bowman : a Union boy's war story - McGowen, Tom (Historical fiction adventures, 2008)
At the age of seventeen, Jesse Bowman of Chicago joins the Union Army to fight in the Civil War, having only a romantic notion of what war is all about, but once he enlists he learns about both the tedium of daily life as a soldier and the hardships and cruelty of battle.